Studies on properties of rice straw/polymer nanocomposites based on polycaprolactone and Fe₃O₄ nanoparticles and evaluation of antibacterial activity - Khandanlou, Roshanak; Ahmad @ Ayob, Mansor; Shameli, Kamyar; Saki, Elnaz; Kalantari, Katayoon (MDPI AG, 2014)
Modified rice straw/Fe3O4/polycaprolactone nanocomposites (ORS/Fe3O4/ PCL-NCs) have been prepared for the first time using a solution casting method. The RS/Fe3O4-NCs were modified with octadecylamine (ODA) as an organic modifier. The prepared NCs were characterized by using X-ray powder diffraction (XRD), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), Thermogravimetric analysis (TGA) and Fourier transform infrared spectroscopy (FT-IR). The XRD results showed that as the intensity of the peaks decreased with the increase of ORS/Fe3O4-NCs content in comparison with PCL peaks, the Fe3O4-NPs peaks increased from 1.0 to 60.0 wt. %. The TEM and SEM results showed a good dispersion of ORS/Fe3O4-NCs in the PCL matrix and the spherical shape of the NPs. The TGA analysis indicated thermal stability of ORS/Fe3O4-NCs increased after incorporation with PCL but the thermal stability of ORS/Fe3O4/PCL-NCs decreased with the increase of ORS/Fe3O4-NCs content. Tensile strength was improved with the addition of 5.0 wt. % of ORS/Fe3O4-NCs. The antibacterial activities of the ORS/Fe3O4/PCL-NC films were examined against Gram-negative bacteria (Escherichia coli) and Gram-positive bacteria (Staphylococcus aureus) by diffusion method using nutrient agar. The results indicated that ORS/Fe3O4/PCL-NC films possessed a strong antibacterial activity with the increase in the percentage of ORS/Fe3O4-NCs in the PCL.